MAKASSAR LANGUAGE AND SELAYAR LANGUAGE COMPARATIVE HISTORICAL COMPARATIVE LINGUISTIC REVIEW: LEXICOSTATISTICS - Solihat, Ilmi; Muldawati, Muldawati (JURNAL KONFIKS, 2025)
Makassar and Selayar languages are assumed to have a gap in kinship. Whereas, in reality, the two languages are not completely identical. The purpose of the study is to analyze Makassar and Selayar languages from the level of kinship and time of separation, influencing factors, and their limitations. The researcher usesmixed methods. Quantitative methods through lexicostatistics techniques and grotochronology techniques, while qualitative methods are used for data collection techniques using listening, recording, and recording techniques and interviews with informants. Primary sources in the form of MS speaker informants aged 60 years, DM aged 58 years, and aged 50 years, from these informants validated from secondary sources, namely the Swadesh vocabulary list and the Makassar and Selayar language dictionaries. Data analysis in this study by applying the steps that must be used in comparative historical research. The results of kinship 64.5% of the kinship level falls into the category of family language levels(family). Mean while, the results of calculating the separation time in centuries are included in the category of Language Dialect levels. (Dialect of language) because the separation time is 360 years in the 0-5 century classification. Factors that influence kinship such as origin and history, cultural influences, structural differences, language use and maintenance. Limitations require considerations such as language borrowing, careful analysis of cognates and consideration of historical language contact, as well as language change.